The UAW's southern gamble : organizing workers at foreign-owned vehicle plants - Silvia, Stephen J. (ILR Press, an imprint of Cornell University Press, 2023)
"This book assesses the United Auto Workers efforts to organize foreign vehicle plants in the South since 1989. It chronicles increased transnational union cooperation and the development of an employers' union avoidance playbook. It shows local politicians fought unionization to preserve their powerbase and that US labor law fails workers."--